Variability of acute physiological responses and performance profiles of youth soccer players in small-sided games - Hill-Haas, S.; Coutts, A.; Rowsell, G.; Dawson, B. (Journal of Science and Medicine in Sport, 2008)
The aim of this study was to examine the variability in physiological and perceptual responses and time-motion profiles of various small-sided soccer game (SSG) formats (2 versus 2, 4 versus 4 and 6 versus 6 players) and regimes (interval and continuous). Typical error (TE) was calculated for mean heart rate as a percentage of maximum heart rate (%HRmax), global ratings of perceived exertion (RPE), blood lactate [La-] and various time-motion characteristics for 16 male soccer players (mean 16.2 years, range 15.6-17.9). The TE for HR responses were <5% for all SSGs. RPE also demonstrated small variability across all SSGs, with TE ranging between 1 and 2 units. In contrast, the TE% for [La-] was higher, ranging from 16% (2 versus 2-interval) to 34% (4 versus 4-interval). The TE% for total distance (TD) and distance covered at 0-6.9 km/h was <5% for all SSGs, with 2 versus 2 interval and continuous games recording the lowest TE (2.2% and 2.9%, respectively). An increase in game format size does not appear to influence the variability of the acute physiological responses to SSGs, although continuous formats display less variability than interval formats. The TD, distance covered and percentage of total time moving at 0-6.9 km/h demonstrated small variability across all formats and regimes. However, higher movement speeds zones (>8 km/h) reflected increased variability, irrespective of game format or regime. Collectively, these results suggest that SSG training can provide a reliable aerobic training stimulus.